2018
DOI: 10.1371/journal.pone.0194699
|View full text |Cite
|
Sign up to set email alerts
|

All three quinone species play distinct roles in ensuring optimal growth under aerobic and fermentative conditions in E. coli K12

Abstract: The electron transport chain of E. coli contains three different quinone species, ubiquinone (UQ), menaquinone (MK) and demethylmenaquinone (DMK). The content and ratio of the different quinone species vary depending on the external conditions. To study the function of the different quinone species in more detail, strains with deletions preventing UQ synthesis, as well as MK and/or DMK synthesis were cultured under aerobic and anaerobic conditions. The strains were characterized with respect to growth and prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 63 publications
3
24
0
Order By: Relevance
“…Here, we characterized three genes, ubiTPa (PA3911), ubiUPa (PA3913) and ubiVPa (PA3912) as essential for the anaerobic UQ9 biosynthesis in P. aeruginosa and dispensable for the aerobic one. These genes are homologs to the ubiT, ubiU and UbiV previously identified in E. coli, which grows normally in anaerobic conditions in a UQindependent manner because of the presence of naphthoquinones (9) (28) (29). In contrast, we demonstrated that these three genes were essential to anaerobic denitrification metabolism of P. aeruginosa, which is in agreement with the presence of a single quinone corresponding to UQ.…”
Section: Discussionsupporting
confidence: 82%
“…Here, we characterized three genes, ubiTPa (PA3911), ubiUPa (PA3913) and ubiVPa (PA3912) as essential for the anaerobic UQ9 biosynthesis in P. aeruginosa and dispensable for the aerobic one. These genes are homologs to the ubiT, ubiU and UbiV previously identified in E. coli, which grows normally in anaerobic conditions in a UQindependent manner because of the presence of naphthoquinones (9) (28) (29). In contrast, we demonstrated that these three genes were essential to anaerobic denitrification metabolism of P. aeruginosa, which is in agreement with the presence of a single quinone corresponding to UQ.…”
Section: Discussionsupporting
confidence: 82%
“…Quantification of transcript levels based on qRT-PCR was performed as described previously (Nitzschke and Bettenbrock, 2018). About 1.5 × 10 9 cells from exponential growth phase were quenched in twice the volume of RNAprotect Bacterial Reagent (Qiagen, Hilden, Germany), vortexed for 5 s and incubated at room temperature for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…(D)MK are considered anaerobic quinones, since they function primarily in anaerobic respiration, whereas UQ is considered an aerobic quinone, because it supplies electrons mostly to the reductases that reduce O 2 (1, 8, 9). Accordingly, UQ is the main quinone of the facultative anaerobe Escherichia coli under aerobic conditions, whereas the naphtoquinones are predominant in the absence of O 2 (10, 11), with UQ nevertheless being present.…”
Section: Introductionmentioning
confidence: 99%